Is Timing Everything? Disability Onset of Youth and Their Outcomes As Young Adults. (September 2014) - Mann, David R.; Honeycutt, Todd C.
The accumulation of human capital during childhood and adolescence greatly influences the value employers place on youth as they transition into the adult labor market. Disabilities acquired prior to adulthood have the potential to disrupt this critical human capital accumulation. This study examines how disability onset among youth affects their education and employment outcomes as young adults. We find that youth with limiting disabilities—especially mental limiting impairments—have poorer labor market and human capital outcomes than their peers without limitations. We also discover some evidence that youth with persistent or later onset disabilities have poorer outcomes than those whose disabilities dissipate as they become adults. These findings suggest that surveys targeting youth and young adults should consider including better measures of disability onset and mental impairment status to understand the disability characteristics of this population.